Angular Velocity Analysis of an Epicyclic Gear Train Using Fundamental Circuits and a Block Diagram - Wu, Yi-Chang; Tsai, Mi-Ching (Proceedings of Engineering and Technology Innovation, 2017)
The prediction of angular velocity is a prerequisite to investigate the power flow and mechanical efficiency of an epicyclic gear train. This paper presents a useful tool, which combines the fundamental circuit and a block diagram, to analyze the angular velocity of an epicyclic gear train. It is a visualized and straightforward method without manipulating tedious kinematic equations, which makes the angular velocity analysis of epicyclic gear trains more simplified. A compound epicyclic gear train used in a synchronous differential device is taken as an example to demonstrate the analysis process of the proposed approach. The velocity ratio of the epicyclic gear train is also derived.